Book review: Adadurov Vadim, Babinskyi Anatoliy, Zaitsev Oleksandr. Images of Metropolitan Andrey Sheptytskyi in journalism and historiography of the Ukrainian diaspora, 1944–1989. / Collective monograph edited by Vadim Adadurov. Lviv: UKU Publishing Hous - Yeremieiev, Pavlo (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
Book review:Adadurov Vadim, Babinskyi Anatoliy, Zaitsev Oleksandr. Images of Metropolitan Andrey Sheptytskyi in journalism and historiography of the Ukrainian diaspora, 1944–1989. / Collective monograph edited by Vadim Adadurov. Lviv: UKU Publishing House, 2023. 260 p. ISBN 978-617-7608-64-5